The efficacy and feasibility of incorporating a standing workstation for perceived low back pain and disability, among call centre workers : a pilot single case study - Maart, Shaun D. (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScPhysio)--Stellenbosch University, 2019.